Analyzing pronunciation content and teaching techniques in grade 5 English textbook - Alya Navi Hanunna; Kalisa, Pasca (ELT Forum: Journal of English Language Teaching, 2025)
Pronunciation is an often neglected but also an important aspect of teaching English to young learners, especially in contexts where English is a foreign language. Although textbooks serve as the primary source in Indonesian elementary schools, their support for pronunciation instruction has not been adequately researched. This study investigated the representation of pronunciation instruction in the English textbook My Next Words Grade 5 published by the Indonesian Ministry of Education and Culture. Using a mixed embedded design, qualitative content analysis was conducted on ten content units within the book, complemented by descriptive quantitative analysis and semi-structured interviews with two experienced elementary school English teachers who used the related textbook. The results revealed a predominant use of mechanical techniques—primarily repetition and choral modeling—that primarily focus on segmental features. Suprasegmental features such as stress and intonation were minimally represented. Classroom implementation was largely teacher-led, with limited use of pair or group work. Interviews with experienced elementary school teachers confirmed that while textbooks offer some basic pronunciation support, significant gaps remain in terms of scaffolding, instructional clarity, and the use of interactive strategies. This study concludes that pronunciation instruction in textbooks still needs further development and recommends improvements such as the need for a textbook design that cover both segmental and suprasegmental features, provides phonetic transcriptions for the targeted vocabulary, and equips it with ready-to-use multimodal resources such as direct links to audio/video resources for effective delivery, and more diverse communicative pronunciation activities.